2019
DOI: 10.1038/s41440-019-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UCHL1 by LDN-57444 attenuates Ang II–Induced atrial fibrillation in mice

Abstract: Atrial fibrillation (AF) is the most common human arrhythmia in clinical practice and may be promoted by atrial inflammation and fibrosis. Ubiquitination is an important posttranslational modification process that is reversed by deubiquitinating enzymes (DUBs). DUBs play critical roles in modulating the degradation, activity, trafficking, and recycling of substrates. However, less research has focused on the role of DUBs in AF. Here, we investigated the effect of ubiquitin C-terminal hydrolase 1 (UCHL1), an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The role of UCHL1 relies on the context of the cells. The antifibrotic role of LDN on the heart was also shown by another study that examined atrial fibrillation but did not use cell culture models 27 . In addition, the pro-activation effect of UCHL1 is observed in other types of fibroblasts, such as cancer-associated fibroblasts and hepatic stellate cells 29,32 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The role of UCHL1 relies on the context of the cells. The antifibrotic role of LDN on the heart was also shown by another study that examined atrial fibrillation but did not use cell culture models 27 . In addition, the pro-activation effect of UCHL1 is observed in other types of fibroblasts, such as cancer-associated fibroblasts and hepatic stellate cells 29,32 .…”
Section: Discussionmentioning
confidence: 73%
“…To date, only a few studies have assessed the role of UCHL1 in heart diseases. One study found that UCHL1 was markedly upregulated in post-MI heart 26 and another suggested that UCHL1 acts as a regulator of the Ang II-induced atrial fibrillation and inhibition of it attenuated atrial fibrosis in vivo 27 . Inspired by the finding that the UCHL1 exerts both endogenous and exogenous pro-activation effects in hepatic stellate cells, which are a type of fibroblast 28,29 , we hypothesised that UCHL1 may promote cardiac fibrosis following MI via induction of CF activation.…”
mentioning
confidence: 99%
“…Expression of ERRFI1 [191], ALOX12 [192], SOCS5 [193], DDIT4 [194], DUSP4 [195], IL6ST [196], DUSP1 [197], SMAD1 [198], NCL (nucleolin) [199], METTL14 [200], FMOD (fibromodulin) [201], CYGB (cytoglobin) [202], UNC5A [203] and TAAR9 [204] are associated with prognosis in patients with diabetic nephropathy, but these genes might be novel target for T1DM. A previous study reported that FAP (fibroblast activation protein alpha) [205], EYA4 [206], BCL9 [207], IRF2BP2 [208], EGR3 [209], GADD45B [210], DMD (dystrophin) [211], LSR (lipolysis stimulated lipoprotein receptor) [212], DLL4 [213], SUN2 [214], SOS1 [215], PIK3CA [216], GAMT (guanidinoacetate N-methyltransferase) [217], RBM47 [218], HSP90AA1 [219], GAB1 [220], S1PR1 [221], EDNRB (endothelin receptor type B) [222], NFKBIA (NFKB inhibitor alpha) [223], GJA1 [224], GADD45G [225], PHLDA1 [226], CMPK2 [227], FIGN (fidgetin, microtubule severing factor) [228], KCNJ2 [229], ABCC9 [230], DIRAS3 [231], EPHX1 [232], RAB4A [233], UBIAD1 [234], CASQ2 [235], TTN (titin) [236], KCNH1 [237], JPH2 [238], OXGR1 [239], UCHL1 [240], SERPINA3 [241], MMP28 [242], ADAMTS2 [243], P2RY1 [244], CSF2RA [245], MYO1F [246], SELPLG (selectin P ligand) [247] and SAMHD1 [248] are expressed in cardiovascular disease, but these genes might be novel target for T1DM. MAOB (monoamine oxidase B) [249], VEGFC (vascular endothelial growth factor C) [250], DBP (D-box binding PAR bZIP transcription factor) [251], MYADM (myeloid associated differentiation marker) [252], NES (nestin) [253], SMURF1 [254], EDNRB (endothelin receptor type B) [255], MUC6 [25...…”
Section: Discussionmentioning
confidence: 99%
“…Matuszczak et al (2018) found that UCHL1 may reflect the metabolic response to acute state inflammation in appendicitis patients. Bi et al (2020) found that UCHL1 inhibitor reduced inflammatory cell infiltration in mouse heart. Furthermore, UCHL1 expression was significantly higher in several inflammatory diseases of glomeruli (Y. Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%